Rising to the challenge: Pharmacy residents on the front lines during COVID-19 pandemic. (6th August 2020) - Uchida, Emma; Long-Fazio, Bianca; Marshall, John; Fortier, Christopher
Abstract: Purpose: To provide pharmacy residents' perspective on how the department of pharmacy at a large academic medical center prepared and managed the surge in admissions of patients with coronavirus disease 2019 (COVID-19), to describe how residents were trained for intensive care unit (ICU) staffing, and to provide recommendations on how residency programs nationally could navigate a second wave of COVID-19 admissions or other disaster response situations. Summary: The majority of postgraduate year 1 (PGY1) pharmacy residents at the institution were trained for ICU staffing and deployed throughout the hospital to ICU units converted to dedicated COVID-19 ICUs to assist in patient care. The training process included live videoconference lectures about relevant ICU topics and on-site experiences with critical care clinical pharmacists. Based on their experience in training for and participating in ICU care of patients with COVID-19, the pharmacy residents recommend considering additional cross-training of residents, integration of additional clinical education, creation of opportunities for resident involvement in telehealth, advancement of residents' roles in emergency responses, building robust mental health services, and continued advocacy for the advancement of pharmacists' and pharmacy residents' scope of practice. Conclusion: The onset of the COVID-19 pandemic caused the institution to reevaluate the allocation of resources, and the department of pharmacy elected to deploy PGY1 pharmacy residents with previous ICU experience to assist in caring for an ICU patient census that had doubled. This experience will be valuable in preparing for another potential wave of COVID-19 cases and a surge in admissions of other groups of patients who deferred care due to the pandemic.